A ação de direito material em face do direito fundamental à jurisdição - Nogueira, Pedro Henrique Pedrosa (2006)
The fundamental right to the jurisdiction is the prerogative that all subject it possess to demand of the State the jurisdictional guardianship, having origin, in the Brazilian law, the extracted norm of the statement of art. 5º, XXXV of the Brazil’s Constitution. In the doctrine, the term "action" has been used indistinctly to assign the material and procedural actions and the right to the jurisdiction, generating ambiguities. Recently, the theory of the action of material law has being questioned and the state monopoly in the distribution of justice, generator of the right to the jurisdiction and the abstract procedural action, would be the reason of its elimination. Our inquiry, is based on the theory of the juridical fact of Pontes de Miranda, searched to approach the law to the jurisdiction, not as a guarantee, but as an independent fundamental right, and also to demonstrate the subsistence of the action of material law as standing to juridical authority aggregated to the subjective rights to impose its accomplishment it accomplishes, differentiated of the "procedural action", used for fundamental right to the jurisdiction exercise’s. The theory of the action of material law contributes for Legal Science, making possible a different vision in the understanding and solution of theoretic problems and is presented useful as a tool in the judicial application of the law to the concrete cases. The study it made possible to ratify the assertive one of that the fundamental right to the jurisdiction did not exclude the action of the plan of the material law, only suppressed its auto-exercise, putting the State in the function to carry through it through the process authoritarianly.